Business Intelligence Implementation for Groceries Commodity Price Data Analytics - Fathe Hibatulwafi; Taufik Asmiyanto (SINTECH (Science and Information Technology) Journal)
As a startup company specializing in agricultural technology, currently PT XYZ does not have any effective and integrated tools to analyze groceries commodity for purchase and sale data-driven decision making. This research will integrating multiple data sources for accurate analysis, tailoring the business intelligence (BI) system to PT XYZ’s specific needs, and developing a robust solution that supports comprehensive decision-making. BI implementation solution will be developed using Pentaho Data Integration & Apache Superset. Applied research used as its method, that contains processes to gather user requirements to gather user needs from each information, design the solution, and dashboard development. The study focused on analyzing data from both internal sources, such as purchase and sales transactions, and external sources, including market price data, using these BI tools to provide comprehensive insights. The developed dashboard contains several sections that allow users to see price recommendation price and get the insight for the last seven days trend, monitor the market position, see team performance, and find the summary about estimated and actual margin comparison. Pentaho successfully handled ETL and data modeling, while Apache Superset enabled straightforward dashboard setup, though chart customization is limited.